Cyber Attacks on Financial Performance: Sharia and SDGs Perspective - Hartutik Hartutik; Dwi Nita Aryani (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The objective of this study is to analyse the impact of cyber-attacks on the performance stability of Bank Syariah Indonesia (BSI) on  financial and non-financial performance indicators, including Capital Adequacy, Asset Quality, Management Quality, Income, and Liquidity. The research method employed is descriptive qualitative, with trend analysis conducted based on secondary data from BSI's annual and quarterly reports prior to and following the cyberattack incident. The findings indicated an upward trend in several performance indicators, reflecting the resilience of the financial performance despite the cyber-attack. BSI was able to maintain customer trust and recorded an increase in both sources of funds and assets. Furthermore, the research evaluated BSI's Shariah compliance and its contribution to the achievement of Sustainable Development Goal (SDG) 16, which focuses on strengthening inclusive, transparent, and accountable institutions. BSI's risk management was found to be at the composite level 2 (low-moderate). It is recommended that improvements be made to the cybersecurity systems, risk management, and the supervision of the Sharia Supervisory Board (DPS) in order to ensure the sustainability of Sharia compliance in every aspect of operations.